Emerging Therapies of Anemia of Chronic Kidney Disease - Dutta, Pradip Kumar; Dutta, Arup (Journal of Chittagong Medical College Teachers' Association, 2012)
Anaemia appears in CKD in all stages. Erythropoietin deficiency and both absolute and relative deficiency of iron are the major causes of this type of anaemia. Erythropoietin deficiency occurs due to decreased renal mass and iron deficiency occurs due to either absolute lack of available iron or increased demand of iron by bone marrow when stimulated by erythropoietin. Correction of anaemia in CKD demands either replacem ent of erythropoietin and or more iron intake. Currently available Erythropoietins are parenteral preparations. They have though negligible but some adverse effects like pure red cell aplasia. Scientist were in search of erythropoietin or erythropoietin like substances which can be given orally and without side effect like pure red cell aplasia. This is the basis of discovery of two newer erythropoietin stimulating agents. These are erythropoietin mimetic peptide (peginesatide) given parenterally and hypoxia inducible factor stabillzer given orally. This review will focus on these two emergent therapies of anaemia in chronic kidney disease which are still going through phase II or phase III trial. JCMCTA 2011; 22(2): 53-56